Coiled Bodies and U2 snRNA Genes Adjacent to Coiled Bodies Are Enriched in Factors Required for snRNA Transcription - Schul, Wouter (The American Society for Cell Biology, 1998)
A significant percentage of the gene clusters that contain the human genes for U1 small nuclear RNA (snRNA) or for U2 snRNA have been found associated with small nuclear domains, known as coiled bodies. We show here, by immunofluorescent labeling of human cells, that coiled bodies are enriched in factors required for the transcription of these snRNA genes. The 45-kDa γ-subunit of the transcription factor, proximal element sequence-binding transcription factor (PTF), which is specific for the snRNA genes, was found in high concentrations in coiled bodies, along with the general transcription factor TATA-box binding protein and a subset of RNA polymerase II. We show that the transcription factors and RNA polymerase II are concentrated in irregularly shaped domains that not only overlap with coiled bodies but also extend to their immediate surroundings. Fluorescent in situ hybridization showed that these domains can overlap with U2 snRNA genes adjacent to coiled bodies. In addition, we found the domains to contain newly synthesized RNA, visualized by 5-bromo-uridine triphosphate labeling. Our data suggest that coiled bodies are involved in the expression of snRNA genes, which leads us to propose the model that coiled bodies are associated with snRNA genes to facilitate and regulate their transcription. These findings point to a general principle of higher order organization of gene expression in the nucleus.